Pyramiding of resistance genes Sr36 and Sr2 in durum wheat background (HI 8498) through marker assisted selection for resistance to stem rust race 117- group pathotypes - Sai Prasad S.V.; Singh S.K.; Kumar V.; Kantwa S.L.; Dubey V.G.; Ambati D.; Prakasha T.L.; Mishra A.N. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Stem rust (Puccinia graminis f. sp. tritici) has historically been one of the major constraints in realizing stabilized durum wheat yields in central India. Pyramiding of genes into a single genotype has been one of the preferred strategies in wheat rusts management. Currently, HI 8498 (Raj 6070/Raj 911) is the most popular durum wheat cultivar in central India. However, it is susceptible to a number of Indian pathotypes of stem rust race 117-group. Hence, a planned breeding programme was taken up to develop derivatives of HI 8498 with improved resistance by pyramiding stem rust resistance genes Sr36 and Sr2 through marker assisted selection. These were targeted as besides being broad-spectrum resistance genes, they have had their origin in tetraploid wheats, Sr36 in Triticum timopheevii and Sr2 in T. turgidum var. durum. While, durum wheat genotype IWP 5070 was chosen as donor parental line for Sr2 gene, based on the presence of ‘pseudo-black chaff (pbc)’, a tightly linked phenotypic marker; Australian bread wheat variety ‘Songlen’ was used as donor for Sr36, since none of the 75 durum wheat genotypes tested was found positive for this gene using tightly linked co-dominant microsatellite marker Xstm773-2. Moreover, Songlen is known to carry Sr2 gene as well. The markers being used for foreground selection in the HI 8498 derivatives are ‘pbc’ and CAPS marker csSr2 for the gene Sr2 and SSR marker Xstm773-2 for the gene Sr36. The stem rust resistance in the ‘HI 8498’ derivatives (BC3F1) carrying Sr2 and Sr36 individually has improved significantly (terminal disease severity 0 to 5S), compared to the background cultivar HI 8498 (30S – 40S). Furthermore, a total of 770 representative SSR markers distributed throughout the wheat genome were screened for polymorphism between parental genotypes HI 8498, Songlen and IWP 5070. Of these, 165 markers showed polymorphism and are being used as effective markers in Marker Assisted Background Selection (MABS) to identify 99 % of recurrent parent genome (RPG) i.e., HI 8498 in BC3F1 generation of both the populations involving Sr36 and Sr2 genes to facilitate their pyramiding in common recipient parent background.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)